PENGARUH TERPAAN IKLAN TOKOPEDIA X BTS DI TELEVISI TERHADAP PERILAKU KONSUMTIF MAHASISWA FIKOM UNIVERSITAS JAYABAYA - Donny Rendi Mung Pujanarko Mega Ayu Permatasari (Universitas Jayabaaya, 2022)
The purpose of this study was to determine whether there was an influence between the exposure of Tokopedia X BTS advertisements on television to the consumptive behavior of FIKOM students at Jayabaya University, as well as to determine how much influence the exposure of Tokopedia X BTS advertisements on television to the consumptive behavior of FIKOM students at Jayabaya University. The theory used is the Stimulus-Organism-Response (SOR) theory. The method used in this research is a survey method with quantitative research. The results of this study indicate that there is a significant influence between the exposure of Tokopedia x BTS advertisements on television to the consumptive behavior of FIKOM students at Jayabaya University.